Subcutaneous abdominal adipose tissue blood flow: variation within and between subjects and relationship to obesity. - Summers, L; Samra, J; Humphreys, S; Morris, R; Frayn, K (1996)
1. We assessed the variation in subcutaneous abdominal adipose tissue blood flow within and between subjects and investigated whether it is correlated with body mass index. 2. We measured body mass index and subcutaneous abdominal adipose tissue blood flow in 38 fasting subjects on the same day and on different days and, in a subgroup of 16 subjects, after a mixed meal. 3. In 190 measurements in the fasted state, subcutaneous abdominal adipose tissue blood flow was significantly more variable between subjects than could be accounted for by the within-subject variation alone. Subcutaneous abdominal adipose tissue blood flow was also significantly more variable between days within subjects than could be accounted for by within-day variation alone. Fasting and post-prandial subcutaneous abdominal adipose tissue blood flow were negatively correlated with body mass index, as was the post-prandial rise in subcutaneous abdominal adipose tissue blood flow. Multiple regression analysis showed that fasting blood flow was not dependent on insulin concentration after allowing for body mass index. There was no correlation between post-prandial subcutaneous abdominal adipose tissue blood flow and insulin concentration. 4. Insulin does not appear to have a direct vasodilatory effect in subcutaneous adipose tissue. Obese subjects have lower fasting and post-prandial subcutaneous abdominal adipose tissue blood flow. This may be because of a blunted response to sympathetic stimulation, or it may be another aspect of the insulin-resistant state.